Systematic Literature Review: Improving Performance in Educational Institutions Through the Balanced Scorecard - Achmad Zailani; Wan Jamaluddin Z; Achi Rinaldi (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
The level of achievement of these goals can be determined through performance measurement. Performance is an overview of the level of achievement in implementing an activity, program, or policy to realize the organization's targets, objectives, mission, and vision as outlined in its strategic planning (Mahsun, 2006: 25). The Balanced Scorecard is a strategic management system that transforms an organization's vision into a set of integrated performance measures. This system ensures a balance between outcome measures and future performance drivers, as well as between internal and external performance. Performance measurement in educational institutions often focuses too heavily on short-term financial or academic aspects, making it less capable of reflecting the institution's readiness to face changing times. To achieve sustainability and ideal educational quality, it is necessary to improve performance in educational institutions through the Balanced Scorecard approach.